Softening the ultra-stiff: Controlled variation of Young's modulus in single-crystal diamond by ion implantation. (1st September 2016) - Battiato, A.; Lorusso, M.; Bernardi, E.; Picollo, F.; Bosia, F.; Ugues, D.; Zelferino, A.; Damin, A.; Baima, J.; Pugno, N.M.; Ambrosio, E.P.; Olivero, P.
Abstract: A combined experimental and numerical study on the variation of the elastic properties of defective single-crystal diamond is presented for the first time, by comparing nano-indentation measurements on MeV-ion-implanted samples with multi-scale modeling consisting of both ab initio atomistic calculations and meso-scale Finite Element Method (FEM) simulations. It is found that by locally introducing defects in the 2 × 10 18 –5 × 10 21  cm −3 density range, a significant reduction of Young's modulus, as well as of density, can be induced in the diamond crystal structure without incurring in the graphitization of the material. Ab initio atomistic simulations confirm the experimental findings with a good degree of confidence. FEM simulations are further employed to verify the consistency of measured deformations with a stiffness reduction, and to derive strain and stress levels in the implanted region. Combining these experimental and numerical results, we also provide insight into the mechanism responsible for the depth dependence of the graphitization threshold in diamond. This work prospects the possibility of achieving accurate tunability of the mechanical properties of single-crystal diamond through defect engineering, with significant technological applications, e.g. the fabrication and control of the resonant frequency of diamond-based micromechanical resonators. Graphical abstract: